Rheological behaviors of Na-montmorillonite considering particle interactions: A molecular dynamics study - Siqi Zhang; Daoyuan Tan; Honghu Zhu; Huafu Pei; Bin Shi (Journal of Rock Mechanics and Geotechnical Engineering, 2025)
Understanding the rheology of bentonite suspensions is crucial for ensuring the safety of engineering practices. However, the rheological mechanisms of bentonite remain unclear due to the limitations of conventional experimental techniques, particularly in assessing the microscopic interactions between clay particles and their impact on rheological properties. In this paper, the rheological behaviors of Na-montmorillonite were studied with a focus on interparticle interactions. Both equilibrium molecular dynamics (MD) and non-equilibrium MD simulations were conducted to understand the physical properties of Na-montmorillonite under zero shear and various shear rates, respectively. The interaction between two parallel clay particles was determined in simulations, indicating that the classical Darjaguin-Landau-Verwey-Overbeek (DLVO) theory underestimates the interactions for a small separation distance. Na-montmorillonite exhibits a typical shear thinning behavior under shearing. However, as water content increases, it begins to behave more like liquid water. The yield stress of montmorillonite, as determined by the Bingham model, was found to be linearly related to the interaction pressures between clay particles. Besides MD simulations, the microstructure of clay suspension was further quantified using the separation distance and incline angle between non-parallel clay particles. Based on MD results and the quantified clay structure, a model was developed to estimate the yield stress of montmorillonite considering various influence factors, including electrolyte concentration, temperature, and solid fraction. Finally, from a comparison with calculated and experimental data, the results confirm the good performance of the proposed model. These findings provide significant insights for understanding the rheological soil behaviors and evaluating the yield stress of bentonite suspensions.